Impact of Modifiable Risk Factors on Long-Term Outcomes after Coronary Artery Bypass Surgery - Leviner, Dror B.; Zafrir, Barak; Jaffe, Ronen; Saliba, Walid; Flugelman, Moshe Y.; Sharoni, Erez (The Thoracic and Cardiovascular Surgeon, 2020)
Background Risk factors control and secondary prevention measures are often reported to be suboptimal in patients undergoing coronary artery bypass grafting (CABG) and may lead to worse clinical outcomes. We aimed to examine potentially modifiable risk factors in patients undergoing CABG and investigate their association with long-term coronary events.Methods Cardiovascular risk factors were recorded preoperatively in the setting of a cardiac catheterization laboratory and were analyzed in relation to long-term coronary events, defined as acute coronary syndrome (ACS) or revascularization after CABG.Results Study population included 1,125 patients undergoing CABG without previous revascularization. Modifiable risk factors included hypertension (71%), hyperlipidemia (67%), diabetes (42%), obesity (28%), and smoking (21%). Only 8% did not have any of the five risk factors. During the mean follow-up of 93 ± 52 months after CABG, 179 patients (16%) experienced a coronary event. Incidence rates were higher in patients with than without the presence of each of the modifiable risk factors, except obesity. Active smoking (hazard ratio [HR]: 1.51; 95% confidence interval [CI]: (1.07–2.13); p = 0.020), presence of diabetes (HR: 1.61; 95% CI: 1.18–2.18; p = 0.002), and hyperlipidemia (HR: 2.13; 95% CI: 1.45–3.14; p < 0.001) were independent predictors of future coronary events after CABG; they also displayed a progressive stepwise increment in the risk of long-term coronary events when cumulatively present.Conclusions In patients undergoing CABG, diabetes, hyperlipidemia, and smoking, as documented preoperatively, were potentially modifiable risk factors that were independently and cumulatively associated with long-term risk of ACS or coronary revascularization, highlighting the importance of early identification and risk factors control for improving cardiovascular health after CABG.
Keywords: coronary artery bypass graft surgery; acute coronary syndrome; risk factors; coronary revascularization; secondary prevention